Discursos contrahegemónicos y « significantes vacíos »: análisis de la influencia de los movimientos sociales poscrisis en las estrategias discursivas de Podemos en España - Laure Beltran (Amnis)
Drawing on the works of Antonio Gramsci, post-Marxist philosophers Ernesto Laclau and Chantal Mouffe consider political struggle as a battle to impose a particular way of perceiving a complex social space on a majority through the development of a system of signifiers to structure it. In their theories, the hegemonic order is the one that succeeds in disseminating this interpretative frame. However, they argue that this symbolization of social reality is the result of an arbitrary and contingent relationship between signifier and signified. From this premise, they advocate the possibility of elaborating counter-hegemonic projects by redefining this relationship. This paper first aims to illustrate these theories through an analysis of the post‑crisis cycle of social mobilization in Spain (2011-2014), considering that these movements allowed for the resemanticization of certain structuring signifiers disseminated by the hegemonic order through their discourses, but also through the experience of renewed political practices. It will then examine to what extent the party Podemos, in seeking to represent this counter-hegemonic project, attempts to reinvest these signifiers in its discourses as they have been redefined to implement a new « common sense » from the institutions.